KELAYAKAN MEDIA FLASH CARD KERAGAMAN JAMUR MAKROSKOPIS DI HUTAN LINDUNG GUNUNGBELABAN TUJUH PADA MATERI KEANEKARAGAMAN HAYATI - Aso, Merlinda Ugha; Yeni, Laili fitri; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to know the feasibility of flash card media variety of macroscopic fungi in Hutan Lindung Gunung Belaban Tujuh, as a learning media on biodiversity material in X SMA. This research consist of two step. First step is making of flash card media and second step is validation of flash card media. The research was quantitative with descriptive method. Flash card media validated by five validators. Two lecture pg biology Education FKIP Untan, and three teacher of biology X SMA/MA. Instrument for validation flash card media using validation sheet comprise of 12 criteria, with analysis data using Content Validity Ratio (CVR) and Content Validity Index (CVI). Based on data analysis of the validation result, flash card media is valid with the value of each Content Validity Ratio (CVR) is 1,00 with CVI Value is 1,00 so flash card media fit to use as a learning media on biodiversity material.Keywords: Flash Card Media, Feasibility, Biodiversity Material.